DEVELOPMENT OF AN INTERACTIVE DIFFERENTIATION TEACHING MODULE WITH IPAS CONTENT AT SDN 1 KUTA CENTRAL LOMBOK - Indraswati, Dyah; Putri, Hikmah Ramdhani; Rahmatih, Aisa Nikmah; Amrullah, Lalu wira zain (STKIP Singkawang, 2024)
This research aims to develop an interactive teaching module for class IV IPAS content at SDN 1 Kuta, Central Lombok. The number of students is 28 sample. The R&D in this research uses the ADDIE model. Data collection used in this research include questionnaires and tests consisting of pretest and posttest. The data analysis in this research uses a Likert scale of 1 to 4. The results of the material expert validity test show an average score of 3.70 categories of very valid. The results of the media expert validity show an average score of 3.29 categories of valid. The teacher response show an average score of 3.75 categories of very practical. The paired t-test shows a difference between the pretest and the post-test score, and because the t-value found is negative, the post-test score is better than the pretest score. The effect size test is in the small category which indicates that even though there are changes, their impact on learning outcomes is limited. The interactive teaching module with differentiated IPAS content that was developed was proven to be suitable for use.